2000
DOI: 10.1038/modpathol.3880098
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Transcription Factor-1 in Normal, Hyperplastic, and Neoplastic Follicular Thyroid Cells Examined by Immunohistochemistry and Nonradioactive In Situ Hybridization

Abstract: Thyroid transcription factor-1 (TTF-1) has been known to regulate the transcriptional activity of thyroid-specific genes. We examined the expression of TTF-1 in non-neoplastic and neoplastic thyroid tissues. By immunohistochemistry, the nuclei of normal and hyperplastic follicular cells strongly reacted with the antibody against TTF-1. Immunohistochemistry also revealed a distinctive nuclear positivity of TTF-1 in all 33 differentiated follicular cell tumors, including 15 follicular adenomas, 5 follicular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 23 publications
4
39
1
3
Order By: Relevance
“…In contrast to the results of Pax8 and TTF-2 staining, our finding of TTF-1 expression in thyroid epithelial neoplasms is in keeping with reported results. 15,21,40 TTF-2 was not expressed in the non-thyroid normal tissues and tumors tested, whereas Pax8 was expressed in B lymphocytes, the renal tubule, epithelial cells of the fallopian tube and ovarian surface inclusion cyst, and tumors of metanephric and gonadal derivation, such as clear renal cell carcinomas, ovarian carcinomas, and seminomas. The latter findings are in keeping with those reported previously.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast to the results of Pax8 and TTF-2 staining, our finding of TTF-1 expression in thyroid epithelial neoplasms is in keeping with reported results. 15,21,40 TTF-2 was not expressed in the non-thyroid normal tissues and tumors tested, whereas Pax8 was expressed in B lymphocytes, the renal tubule, epithelial cells of the fallopian tube and ovarian surface inclusion cyst, and tumors of metanephric and gonadal derivation, such as clear renal cell carcinomas, ovarian carcinomas, and seminomas. The latter findings are in keeping with those reported previously.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, TTF-1 is positive in 75% of lung adenocarcinomas, 14 and almost all cases of well-differentiated thyroid neoplasms of follicular origin. 15 Thorough routine microscopic examination, along with adequate clinical and radiographic information, generally would allow a definitive diagnosis in such a setting. Immunohistochemistry study can further solidify the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated the positivities of galectin-3 in 100% of papillary carcinomas, 90 -100% of follicular carcinomas, 50 -80% of medullary carcinomas, 0 -33% of follicular adenomas and 0 -38% of nodular goitres (Beesley et al, 2002). Thyroid transcription factor-1 also expressed 100% of differentiated follicular tumours including follicular adenoma, follicular carcinoma and papillary carcinoma, but only 25% of undifferentiated carcinoma of the thyroid (Katoh et al, 2000). These markers were often expressed in benign lesions as well as malignant lesions, being due to the different mechanisms from LAR P-subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas arising from lung and thyroid also show frequent TTF-1 expression. 1,2 As the lung is one of the most common sites of metastasis, TTF-1 is considered as a reliable marker to distinguish between primary lung carcinoma and lung metastasis, especially when dealing with an adenocarcinoma or a large-cell carcinoma. [3][4][5][6] It is also considered as a reliable marker in the differential diagnosis between pleural localization of lung origin carcinoma and malignant mesothelioma.…”
mentioning
confidence: 99%